The Influence of Transformational Leadership and Organizational Culture on Employee Performance: Study of One The Companies Operating in The Field of Publishing and Book Trading in The City of Bandung - Farras, M. Faishal; Hadian, Dedi; Hardiyana, Aan (Acman: Accounting and Management Journal, 2024)
This study utilized SPSS 16 software for research analysis. Its objective was to examine the impact of transformational leadership and organizational culture on employee performance. This research intends to analyze the elements that exert the most significant influence on employee performance, specifically the relationship between transformational leadership, organizational culture, and employee performance. The analysis will be conducted utilizing a questionnaire administered to 30 respondents. Research utilizing path analysis indicates that the variable of transformational leadership (X1) exerts a direct influence of 41.3% and an indirect influence through its link with organizational culture (X2) of 12.3%, resulting in a total influence of 53.6%. The variable of organizational culture (X2) has a direct impact of 12.9% and an indirect impact through its association with transformational leadership (X1) of 12.3%. The total impact is 25.2%. The research findings demonstrate that the coefficient of determination (R-square), expressed as a percentage, highlights the significant impact of both transformational leadership (X1) and organizational culture (X2) on the employee performance variable (Y), accounting for 78.8% of the variance. It is important to note that there may be other factors that also influence performance. Employees (Y) who were not included in the study are represented by an epsilon value of 21.2%. The research findings suggest that focusing on transformational leadership and organizational culture can enhance employee performance in a publishing and book trading company located in Bandung. It is recommended that more attention be given to these factors.